The Role of Genistein in Type 2 Diabetes and Beyond: Mechanisms and Therapeutic Potential - Mateusz Kciuk; Weronika Kruczkowska; Katarzyna Wanke; Julia Gałęziewska; Damian Kołat; Somdutt Mujwar; Renata Kontek (Molecules)
The global prevalence of type 2 diabetes mellitus (T2DM) necessitates the exploration of novel therapeutic approaches to mitigate its complex molecular pathogenesis. This review investigates the potential role of genistein, a prominent isoflavone derived from soybeans, in the management of T2DM. Recognized for its selective estrogen receptor modulator (SERM) activity, genistein exerts a multifaceted influence on key intracellular signaling pathways, which are crucial in regulating cell proliferation, apoptosis, and insulin signaling. Genistein’s anti-inflammatory, anti-oxidant, and metabolic regulatory properties position it as a promising candidate for T2DM intervention. This review synthesizes current research spanning preclinical studies and clinical trials, emphasizing genistein’s impact on insulin sensitivity, glucose metabolism, and inflammatory markers. Additionally, this review addresses genistein’s bioavailability, safety, and potential influence on gut microbiota composition. By consolidating these findings, this review aims to provide a comprehensive understanding of genistein’s therapeutic potential in T2DM management, offering valuable insights for future research and clinical practice.